Nutritional assessment of plant-based beverages in comparison to bovine milk - Smith, Nick W.; Dave, Anant C.; Hill, Jeremy P.; McNabb, Warren C. (Frontiers in Nutrition, 2022)
Plant-based beverages (PBB) are often marketed and used by consumers as alternatives to ruminant milks, particularly bovine milk (hereafter referred to as milk). However, much research has established that there is variation in nutritional composition among these products, as well as demonstrating that they are largely not nutritional replacements for milk. A survey of the prices and nutrition labels of PBB available in New Zealand (NZ) supermarkets was undertaken. Selected almond, coconut, oat, rice, and soy PBB products were then analyzed for nutritional content, including energy, fat, protein, amino acid, bioavailable amino acid, and trace element contents. Finally, the protein and calcium contents of well-mixed and unshaken products were analyzed to ascertain the impact of colloidal stability on nutrient content. All PBB groups were more expensive than milk on average, while their declared nutrient contents on package labels was highly variable within and between groups. Analyses of selected PBB revealed that soy products had the most similar proximate composition to milk, while all other PBB groups contained less than 1.1 g protein per 100 mL on average. Many PBB were fortified with calcium to a similar concentration as that in milk. Shaken and unshaken samples showed divergent protein and calcium content for several PBB products but had no effect on the composition of milk, indicating that the nutrient content of PBB at the point of consumption will be dependent on whether the product has been shaken. Only the soy PBB had comparable amino acid content and bioavailability to milk. Overall, our results demonstrate the diversity in composition and nutritional properties of PBB available in NZ. While the existent environmental footprint data on PBB shows that they generally have lower carbon emissions than milk, milk currently accounts for approximately 1% of the average NZ resident’s consumption-based emissions. Except for calcium-fortified soy PBB, none of the commercially available PBB had nutritional compositions that were broadly comparable to milk.